2020
DOI: 10.1016/j.oraloncology.2020.104693
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic & head and neck cancer patients management: The role of virtual multidisciplinary team meetings

Abstract: Oral Oncology xxx (xxxx) xxxx 1368-8375/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…The head and neck region consists of all the sites by which the COVID-19 virus may be transmitted [36]. Thus, people with head and neck malignancy may be at risk of more deleterious consequence of COVID-19 infection [37]. Evidence based on previous studies suggested that people with head and neck malignancy have higher risk of mechanical ventilation or death than people without any malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The head and neck region consists of all the sites by which the COVID-19 virus may be transmitted [36]. Thus, people with head and neck malignancy may be at risk of more deleterious consequence of COVID-19 infection [37]. Evidence based on previous studies suggested that people with head and neck malignancy have higher risk of mechanical ventilation or death than people without any malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence based on previous studies suggested that people with head and neck malignancy have higher risk of mechanical ventilation or death than people without any malignancy. Thus, studies suggested some practical steps such as the use of protective equipment, warranting access to critical drugs, telecommunications technology consultations, and wider community-based supports [15,[36][37][38]. In a cohort of 18 people with a malignancy described that 6% of people with head and neck malignancy had a higher risk of mechanical ventilation (39%) and death (8%) than those people without a history of any malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Since lymphocytopenia is often seen in severe COVID-19 patients, the CRS caused by SARS-CoV-2 virus has to be mediated by leukocytes other than T cells, as in patients receiving CAR-T therapy; a high WBC-count is common, suggesting it, in association with lymphocytopenia, as a differential diagnostic criterion for COVID-19 [14]. In light of the pandemic of COVID-19, which overcame the health systems of countries, which threatens the health of cancer patients from two sides, either in terms of postponing treatment appointments, which is a risk to patients and increases the development of the disease [15], or either cancer patients can be called to hospitals and here the risk of infection and infection with COVID-19 increases [16].…”
Section: Covid-19 Infection and Cancer Diseasesmentioning
confidence: 99%
“…One person as a coordinator can take history and all patient records, such as imaging and lab data, and share it to the rest. By examining the patient's condition and considering the current crisis, a treatment plan can be decided [5].…”
Section: Role Of Virtual Multidisciplinary Team Meetingsmentioning
confidence: 99%
“…Within the field of action of oral and maxillofacial surgeons, the approach and management of oral cancer is one relevant area [4]. Squamous cell carcinoma represents the most common form of head and neck cancer, and its early approach plays a key role in reducing morbidity and mortality [5]. Based on this, the present review aims to collect and to discuss aspects of approaching the management of inpatients and outpatients with oral cancer during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%